1997
DOI: 10.1021/jp970005r
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Spectroscopic Properties of the LH2 Bacteriochlorophyll−Protein Antenna Complex from Rhodopseudomonas acidophila

Abstract: Absorption and CD spectra of a photosynthetic bacterial antenna complex are calculated on the basis of the crystal structure of the LH2 (B800-850) complex from Rhodopseudomonas acidophila. This complex contains a ring of 18 tightly coupled bacteriochlorophylls (B850) and a ring of 9 more weakly coupled bacteriochlorophylls (B800). Molecular orbitals for bacteriochlorophylls with the three different geometries seen in the crystal structure are obtained by semiempirical quantum mechanical calculations (QCFF/PI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
374
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(398 citation statements)
references
References 79 publications
24
374
0
Order By: Relevance
“…3 In our simulations of the B850 absorption band we have taken into account the interactions between the Q y transitions of BChls, neglecting their mixing with Q x , B y , B x transitions as well as with charge transfer states. 8 We supposed that the interaction energies between the BChl molecules are M 12 ) 400 cm - 16 For the LH2 complex of Rb. sphaeroides an analysis of the CD spectrum yielded M 12 ) 300 cm -1 and M 23 ) 233 cm -1 .…”
Section: Model Of the Bacterial Light-harvesting Antennamentioning
confidence: 99%
“…3 In our simulations of the B850 absorption band we have taken into account the interactions between the Q y transitions of BChls, neglecting their mixing with Q x , B y , B x transitions as well as with charge transfer states. 8 We supposed that the interaction energies between the BChl molecules are M 12 ) 400 cm - 16 For the LH2 complex of Rb. sphaeroides an analysis of the CD spectrum yielded M 12 ) 300 cm -1 and M 23 ) 233 cm -1 .…”
Section: Model Of the Bacterial Light-harvesting Antennamentioning
confidence: 99%
“…14, [18][19][20][21][22][23][24][25][26][27][28][29][30] Various spectroscopic measurements, such as absorption, 4,5 fluorescence, 11,12 pump-probe, 12 and photon echo, 6,7 have been employed for probing exciton motions in molecular aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…In this equation, the Lorentz correction factor is used (20). Using this formula, we found that integration over the Voigt-type absorption band previously described, provides a transition dipole moment of (5.2 Ϯ 0.5) D for BChl-ser in PBS, pH ϭ 7.4.…”
Section: Solvent Effects On the Absorptionmentioning
confidence: 87%